The Interaction Between CitMYB52 and CitbHLH2 Negatively Regulates Citrate Accumulation by Activating CitALMT in Citrus Fruit - Liu, Shengchao; Liu, Xincheng; Gou, Bangrui; Wang, Dengliang; Liu, Chunrong; Sun, Jun; Yin, Xueren; Grierson, Donald; Li, Shaojia; Chen, Kunsong (Frontiers in Plant Science, 2022)
Citric acid plays significant roles in numerous physiological processes in plants, including carbon metabolism, signal transduction and tolerance to environmental stress. For fruits, it has a major effect on fruit organoleptic quality by directly influencing consumer taste. Citric acid in citrus is mainly regulated by the balance between synthesis, degradation and vacuolar storage. The genetic and molecular regulations of citric acid synthesis and degradation have been comprehensively elucidated. However, the transporters for citric acid in fruit are less well understood. Here, an aluminum activated malate transporter, CitALMT, was characterized. Transient over-expression assay and stable transformation of CitALMT significantly reduced citrate concentration in citrus fruits and transgenic callus, correspondingly, transient RNA interference-induced silencing of CitALMT increased citrate significantly, indicating that CitALMT plays an important role in citrate accumulation in citrus fruits. In addition, dual-luciferase assays indicated that CitMYB52 and CitbHLH2 could trans-activate the promoter of CitALMT. Among them, CitbHLH2 could physically interact with the E-box motif in the CitALMT promoter by EMSA analysis. Bimolecular fluorescence complementation assays, Yeast-two hybrid, coimmunoprecipitation and transient over-expression and RNAi assay indicated that the interaction between these two transcription factors could synergistically trans-activate the CitALMT to negatively regulate citrate accumulation.